The influence of the pressure on the microstructure of yttria-stabilized zirconia thin films deposited by dual magnetron sputtering. (March 2016) - Depla, D.; Besnard, A.; Lamas, J.
Abstract: Mixed oxide thin films, such as yttria-stabilized zirconia, deposited by dual reactive magnetron sputtering on a non-rotating substrate show a typical microstructure of bended, or tilted columns. Two effects define the tilt. The first effect is the compositional gradient over each column which results in a different lattice spacing. To accommodate this difference, the column bends. As such, the chemical composition has a major influence on the final columnar tilt. The second effect is ballistic shadowing which is controlled by the pressure-distance product. At higher pressure-distances, this second effect plays a more prominent role, and a different behaviour of the columnar tilt as a function of the film composition is noticed. The experimental trends can be understood by the use of a particle trajectory code which provides the angular and energy distribution of the atoms to a ballistic aggregation Monte Carlo code simulating the resulting microstructure. Highlights: Overview of the microstructure of thin films deposited by dual magnetron sputtering. Correlation between microstructure and pressure for yttria stabilized zirconia. Combination of Monte Carlo particle trajectory and ballistic modelling.